Analisis Komprehensif Dampak Merger terhadap Pertumbuhan dan Inovasi di Bank Syariah Indonesia (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This study analyzes the impact of the merger between three state-owned Islamic banks that formed Bank Syariah Indonesia (BSI) in 2021 on growth and innovation. This merger aimed to create an entity that is stronger and more competitive globally. Using quantitative analysis of BSI’s financial reports before and after the merger along with qualitative insights through interviews with management, this research found significant increases in sales revenue and customer base, from 14 million pre-merger to 19 million post-merger. Although investment income fluctuated, overall financial performance improved. This study highlights the significance of financial report analysis in evaluating merger success and its effects on product and service innovations. With government support and substantial market potential, BSI is expected to contribute significantly to Indonesian Sharia economic development.